The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ma13204627
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Influence of the Chemical Nature of Fillers on Rheological and Fatigue Behavior of Bitumen Emulsion Mastic

Abstract: Cold Bitumen Emulsion (CBE) mixture technologies have been recently developed to lower pavement construction temperatures to reduce environmental costs and control gas emissions. Due to its poor early mechanical strength, active fillers (i.e., cement) have been used to obtain high early stiffness in order to have the potential for timely construction of the next layer. There is, however, a lack of understanding about the impact of active fillers on the viscoelastic behavior and fatigue damage resistance of CBE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Al-Mohammedawi and Mollenhauer 2020 conducted a study on the effect of the chemical nature of fillers (Both acidic and basic fillers) on the mechanical properties of cationic bitumen emulsion mastic. It was found that the filler with basic nature shows high reactivity in terms of pH value which is reflected in the fatigue and rheological performance which was believed due to the high filler/ bitumen emulsion compatibility [53], [64]. However, this study needs to be supported by microscopic and microstructure analysis in order to get more information about the surfactant and bitumen adsorption on filler particles.…”
Section: Preprintsmentioning
confidence: 89%
See 1 more Smart Citation
“…Al-Mohammedawi and Mollenhauer 2020 conducted a study on the effect of the chemical nature of fillers (Both acidic and basic fillers) on the mechanical properties of cationic bitumen emulsion mastic. It was found that the filler with basic nature shows high reactivity in terms of pH value which is reflected in the fatigue and rheological performance which was believed due to the high filler/ bitumen emulsion compatibility [53], [64]. However, this study needs to be supported by microscopic and microstructure analysis in order to get more information about the surfactant and bitumen adsorption on filler particles.…”
Section: Preprintsmentioning
confidence: 89%
“…surfactants' function can therefore be compromised when cement or mineral aggregate engages with cationic emulsions, due to increased pH; cement is particularly potent in affecting the pH of cationic emulsion. Consequently, the setting time and stability of bitumen emulsions are normally gauged concerning active filler [53]. It should be noted in this regard that some surfactants, including quaternary amines, retain their functionality even when pH changes [5].…”
Section: Ph Change Breaking Mechanismmentioning
confidence: 99%
“…Twenty universities and scientific centres contributed with their original research papers to this Special Issue of Materials . The issues covered can be divided into five main topics: Characterization of recycled materials in asphalt concrete mixtures, such as waste of sanitary ceramics [ 23 ], crumb rubber (CR) from waste tires [ 24 , 25 , 26 ] and reclaimed asphalt (RA) [ 27 , 28 ]; Investigation of natural [ 28 ] or bio-based [ 29 ] materials used as rejuvenators in recycled asphalt applications; Study of rheological and fatigue behaviour of bituminous materials with [ 30 ] and without [ 31 ] the use of renewable bio-materials; Evaluation of lubricant characteristics of graphite nanoplatelets [ 32 ]; Fatigue life prediction model for materials employed on long-span steel bridge decks [ 33 ]. …”
Section: Short Description Of the Articles Published In This Special ...mentioning
confidence: 99%
“…It was also observed that the beneficial effect of lime addition in reducing rutting (which is a high temperature phenomenon) was realized more at higher mix temperatures. Al-Mohammedawi and Mollenhauer, [3] identified the influence of active fillers such as limestone, cement, ladle slag, and silica fume on the rheological properties and the resulting fatigue behavior of cold bitumen emulsion mastic. The assessment was supported by chemical analysis for the filler-bitumen emulsion.…”
Section: Introductionmentioning
confidence: 99%